HIV-specific cytotoxic T cells from long-term survivors select a unique T cell receptor. - Dong, T; Stewart-Jones, G; Chen, N; Easterbrook, P; Xu, X; Papagno, L; Appay, V; Weekes, M; Conlon, C; Spina, C; Little, S; Screaton, G; et al. (2004)
HIV-specific cytotoxic T lymphocytes (CTL) are important in controlling HIV replication, but the magnitude of the CTL response does not predict clinical outcome. In four donors with delayed disease progression we identified Vbeta13.2 T cell receptors (TCRs) with very similar and unusually long beta-chain complementarity determining region 3 (CDR3) regions in CTL specific for the immunodominant human histocompatibility leukocyte antigens (HLA)-B8-restricted human immunodeficiency virus-1 (HIV-1) nef epitope, FLKEKGGL (FL8). CTL expressing Vbeta13.2 TCRs tolerate naturally arising viral variants in the FL8 epitope that escape recognition by other CTL. In addition, they expand efficiently in vitro and are resistant to apoptosis, in contrast to FL8-specific CTL using other TCRs. Selection of Vbeta13.2 TCRs by some patients early in the FL8-specific CTL response may be linked with better clinical outcome.